Competence Training for Pharmacy - Jeffrey Atkinson (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The educational system leading up to the pharmacy degree, student training, and the continuing personal development of pharmacists are being more and more mapped to the competences pharmacists require to provide the relevant safe and efficient pharmaceutical services to meet the health needs of patients. This book draws on the experience of experts involved in the develoment of competence training for pharmacy education and training in Europe, North America, and Australia. It discusses the philosophy and implications of such an approach, as well as the production and development of models, and their application to existing courses.